International Conference on Biomedical and Pharmaceutical Sciences, August 27-28, (ICBPS-2022) - World Forum for Young Scientist (International Journal of Natural Medicine and Health Sciences, 2022)
International Conference on Biomedical and Pharmaceutical Sciences 2022 (ICBPS-2022) was successfully held on August 27-28, 2022, by World Forum by Young Scientists (WFYS) on the online platform. Many international invited speakers presented high-quality topics relevant to biomedical sciences to young researchers. It has provided a multidisciplinary point of view for the young to plan their future research and also led the way for them to establish new collaborations. I would like to thank all participants, speakers, and the organizing team for the 2022 series of this wonderful conference event. I am happy to be part of ICBPS-2022 as an organizer and invited speaker. I hope the next version of ICBPS will be organized, and I look forward to it. Kind regards, Prof. Dr. Ilkay ERDOGAN ORHAN Faculty of Pharmacy, Gazi University, Ankara, Turkiye